Study of the Optimized Parameters of Stainless Steel 316L Powder for Rapid Prototyping Based on Selective Laser Melting Technique - Apinya Laohaprapanon (Prince of Songkla University, 2016)
Thesis (M.Eng., Material engineering)--Prince of Songkla University, 2011